Sustainability Performance: Measuring impact of FinTech and Digital Transformation in Future of Green Finance - Tiwari, Ghanashyam; Dhusia Sharma, Neeta (International Research Journal of MMC, 2026)
Bank and financial institutions help to promote sustainable development through the integration of digital technologies and environmentally responsible financial practices. This study investigates the impact of Digital Transformation, FinTech Adoption, and Green Finance on Sustainability Performance in the banking sector, with a focus on an emerging economy context. Using a survey research design primary data were collected from 401 bank employees during July-September 2025.-. A convenience sampling technique was employed, and the data were analyzed using descriptive statistics and structural equation modeling (SEM). The findings revealed that Digital Transformation had the strongest positive effect on Sustainability Performance, followed by Green Finance and FinTech Adoption. These results indicate that the integration of digital systems, technology-driven financial services, and green financing initiatives significantly enhances banks’ economic, environmental, and social performance. The study highlights the importance of adopting an integrated sustainability strategy that aligns technological innovation with green financial practices. From a practical perspective, the findings offer valuable insights for bank managers and policymakers seeking to strengthen sustainability performance through digital and green initiatives. The study contributes to the growing literature on sustainable banking by demonstrating how digital and FinTech-driven innovations can serve as strategic enablers of sustainability in the financial sector.